Exploring Zakat Distribution Via Blockchain in Indonesia Perspective of Maslahah Mursalah Wahbah Zuhaili - Zamroni, Muhamamd Afif; Toha, Mohamad; Zuana, Muhammad Mujtaba Mitra; Baiqun Isbahi, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
To achieve the goal of increasing the effectiveness and efficiency of zakat services, it is very important to have a strong security system in zakat administration. This includes the accurate distribution of zakat money to mustahiq. Blockchain technology is a digital data storage system consisting of several servers, which serves this purpose. This article explains blockchain zakat in Indonesia when viewed with maslahah mursalah according to Wahbah Zuhaili. This study uses a qualitative descriptive method and its type is library research (literature review) with an ushul fiqh approach. The data analysis techniques used in this article are data reduction, data presentation, and conclusion. The results of this study state that Blockchain provides a stimulus for optimizing zakat fund management through basic benefits (maslahah ad-dharuriyah) in the form of maintaining the religion of muzakki to fulfill obligations (hifdz ad-din), and protection of property. up to mustahiq (hifdz al-mal), and maintaining the good name of zakat institutions from slander in zakat governance due to the openness of the system (hifdz al-'ird). The high scope of transactions recorded in the blockchain system, including the collection and distribution of zakat, is smoothness in realizing the welfare of mustahiq and helping the country's economy so that government contribution is needed in supporting the progress of zakat management with blockchain technology.